Music students’ perception of the use of multi-media technology at the graduate level in hong kong higher education - Ho, Wai-Chung (Asia Pacific education review, 2007)
The core purpose of this paper is to draw together research issues and concrete problems with the use of multimedia technology at the graduate level in higher music education by examining one university's responses to the challenges posed by the use of multimedia technology as a teaching and learning aid for music education. Between June and July 2006, this study conducted a simple questionnaire and interview survey of 16 postgraduate students. The results suggest that music students are confident in their abilities to use multimedia technologies but that many do not believe that the introduction of multimedia technologies into the curriculum will improve the quality of their education. Whilst students' motivation to learn depends on their interest in the subject and their lecturer's approach, the incorporation of technology should always be relevant to each individual module. The results of this case study could help other universities respond to the changes brought about by electronic learning and other educational multimedia technology. (Contains 2 figures.)